Tensile Properties of Single Desmin Intermediate Filaments - Kreplak, Laurent (The Biophysical Society, 2008)
Within muscle fibers, desmin intermediate filaments (IFs) are major constituents of the extrasarcomeric cytoskeleton. However, their contribution to the mechanical properties of myocytes has remained elusive. We present an experimental approach to measure the extensibility and the tensile strength of in vitro reconstituted desmin IFs adsorbed to a solid support. The tip of an atomic force microscope (AFM) was used to push on single filaments perpendicular to the filament axis. The torque of the AFM cantilever was monitored during the pushing events to yield an estimate of the lateral force necessary to bend and stretch the filaments. Desmin IFs were stretched up to 3.4-fold with a maximum force of ∼3.5 nN. Fully stretched filaments exhibited a much smaller diameter than did native IFs, i.e., ∼3.5 nm compared to 12.6 nm, both by AFM and electron microscopy. Moreover, we combined the morphological and lateral force data to compute an average stress-strain curve for a single desmin filament. The main features were a pronounced strain-hardening regime above 50% extension and a tensile strength of at least 240 MPa. Because of these nonlinear tensile properties, desmin IFs may dissipate mechanical energy and serve as a physical link between successive sarcomeres during large deformation.